A metodologia de projetos e a educação matemática crítica durante o desenvolvimento de um projeto sobre o desperdício de alimentos na escola - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work presents a research at a graduate course on the application of project methodology in a proposal for critical mathematics education with high school students. The research consisted of carrying out a project on food waste at school with a second year night class from a public school on the north coast of Rio Grande do Sul. The data built for the research consist of students' written materials, a daily report of the teaching practice written by the researcher and a questionnaire answered by students. The theory that supported the analyzes was works focused on critical mathematics education and on project methodology. As the main results of the analysis, the following stand out: the challenges for implementing the project-based teaching methodology, considering all agreements and deadlines established with the school; compromised promotion of critical mathematics education due to time constraints and student engagement with the project; and the manifestations of the ideology of certainty by the confidence attributed to graphs, tables and numbers. Thus, this work sought to contribute to the analysis of yet another teaching practice involving critical mathematics education and project methodology, in order to enrich and encourage the construction of knowledge and discussions on these themes.
Keywords: Metodologia de projetos; Educação matemática crítica; Ideologia da certeza; Ensino Médio; Desperdício de alimentos; Project methodology; Critical mathematics education; Ideology of certainty; High school; Food waste; CNPQ::CIENCIAS EXATAS E DA TERRA